Absent but Accounted for: A New Approach to the Copper Scroll. (20th July 2015) - Weitzman, Steven
Abstract : Like so much of early Jewish literature, the strange Dead Sea scroll known as the Copper Scroll (3Q15) remains suspended somewhere between reality and fantasy. Even before scholars had fully unrolled its copper plates in 1956, they were able to discern that it recorded a list of treasures, but there soon broke out a dispute over whether this treasure was real or not. Some scholars felt that the treasure was too large to be real and that it was a figment of its author's imagination. They sought the origins of the scroll in ancient Jewish legend. Others believed the treasure to be quite plausible, probably connected to the Temple in some way. The scroll itself, however, revealed nothing that might settle the issue in one direction or the other. In what follows, I wish to explore a way beyond this impasse, not resolving whether the treasure was real or not, but suggesting how it could be both at the same time. Such a claim will seem contradictory, but it is my hope over the course of this essay not just to establish the possibility of such a position but to demonstrate that such a reading is actually more consistent with the evidence we have than any reading that imposes an either/or choice between reading the treasure as fictional or genuine.